CENTRALIZATION OF THE FORMING OF NATIONAL AND REGIONAL REGULATIONS, IS IT POSSIBLE? - Rachmat Trijono (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2019)
The forming of regulations in the executive domain is still carried out by institutions spread across various ministries and non-ministries.For this reason, it is necessary to do research of the centralization of the formation of national regulations and regional regulations. The aim of this research is describing centralization national and regional regulations forming. This research is descriptive analytical that aimed at expressing a problem or situation or event as it is so that it can reveal the actual facts. Data types that used in this study is secondary data and primary data. All data is analyzed by qualitative analysis method. The results of the study indicate that the establishment of a legislative ministry can unite the formation of national regulations and regional regulations so as to avoid overlaps and will formed harmonization of national regulations and regional regulations. This research further suggests to establishing ministry of legislation.